Oxford handbook of clinical medicine. - Wilkinson, Ian (Ian Boden) (Oxford : Oxford University Press, 2024)
This handbook is a guiding star for all medical students, junior doctors and trainees. The culmination of more than 20 years' clinical experience, and containing the knowledge and insight gained by more than 15 authors, the new edition is the definitive pocket-sized guide to today's clinical medicine.
This edition also issued in print: 2024.
Previous edition: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on January 5, 2024).
Keywords: Clinical medicine -- Handbooks, manuals, etc; Health and Wellbeing; Clinical & internal medicine